THE SCHOOL’S EFFORTS TO FOSTER A SENSE OF COMMUNITY, INTEGRITY, AND SOCIAL RESPONSIBILITY AMONG STUDENTS AT SD MUHAMMADIYAH 1 WRINGINANOM - Melina Rosalinda; Machful Indra Kurniawan (Academic Journal Research, 2026)
Objective: This study aims to describe the school’s efforts to foster a sence of cooperation, integrity, and social responsibility among students at SD Muhammadiyah 1 Wringinanom. Method: This study employs a qualitative approach with descriptive design. The research subjects include the principal, teachers, and students selected using purposive sampling. Data collection tecniques included observation, interviews, and documentation. Data analysis employed an interactive model comprising data reduction, data presentation, and drawing conclusions. Results: The results indicate that character development is carried out in an integrated manner through intracurricular, cocurricular, and extracurricular activities. The value of cooperation is instilled through group work, classroom duties, and community service. Integrity is developed by fostering honest, disciplined, and responsible attitudes, supported by teachers’ exemplary behavior. Meanwhile, social concern is fostered through socialactivities such as donations and sharing. Supporting factors include teachers’ commitment, the principal’s leadership, and a supportive school culture, while inhibiting factors include student’s backgrounds and limited family support. The conclusion of this study indicates that the school’s efforts in shaping student character have been effective, but require continuous strengthening and consistency. Novelty: The results indicate that character development is carried out in an integrated manner through intracurricular, cocurricular, and extracurricular activities. The value of cooperation is instilled through group work, classroom duties, and community service. Integrity is developed by fostering honest, disciplined, and responsible attitudes, supported by teachers’ exemplary behavior. Meanwhile, social concern is fostered through socialactivities such as donations and sharing.